2007
DOI: 10.1029/2007gl030282
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for interhemispheric stratosphere‐mesosphere coupling derived from noctilucent cloud properties

Abstract: [1] We investigate the link between the cold summer mesopause region and the dynamics in the stratosphere. In particular, we use Odin observations of noctilucent cloud (NLC) properties as a proxy for the state of the summer mesosphere and ECMWF winter stratospheric temperatures as a proxy for the residual circulation in the stratosphere. Large areas of strong anticorrelation between winter stratospheric temperature and summer mesospheric NLC indicate that there is an interhemispheric connection. Timelagged cro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

20
135
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 103 publications
(155 citation statements)
references
References 21 publications
20
135
0
Order By: Relevance
“…7) seasonal inter-hemispheric differences in the subtropics in this altitude region might be anticipated. Recently evidence of an inter-hemispheric coupling between the polar winter stratosphere and polar summer mesosphere has been presented using the mesospheric pole-to-pole circulation as the connecting link (Karlsson et al, 2007;Becker et al, 2004;Becker and Fritts, 2006;Karlsson et al, 2008). These studies suggest a stronger upwelling in the Northern Hemisphere polar summer mesosphere as compared to the Southern Hemisphere, accompanied by a stronger meridional flow towards the Southern Hemisphere winter polar region.…”
Section: Discussion and Summarymentioning
confidence: 86%
“…7) seasonal inter-hemispheric differences in the subtropics in this altitude region might be anticipated. Recently evidence of an inter-hemispheric coupling between the polar winter stratosphere and polar summer mesosphere has been presented using the mesospheric pole-to-pole circulation as the connecting link (Karlsson et al, 2007;Becker et al, 2004;Becker and Fritts, 2006;Karlsson et al, 2008). These studies suggest a stronger upwelling in the Northern Hemisphere polar summer mesosphere as compared to the Southern Hemisphere, accompanied by a stronger meridional flow towards the Southern Hemisphere winter polar region.…”
Section: Discussion and Summarymentioning
confidence: 86%
“…Karlsson et al (2009a) analyzed simulations from the Canadian Middle Atmosphere Model and found that the model reproduces the observed relationship. Karlsson et al (2007Karlsson et al ( , 2009b found a link between variability of PMCs and dynamical variations in the opposite (winter) hemisphere stratosphere. Espy et al (2011) found that the correlation varied with the phase of the QBO in tropical stratospheric zonal wind.…”
Section: Teleconnections Involving Zonal Mean Winds and Planetary Wavesmentioning
confidence: 99%
“…Liu and Roble 2002;Tan et al 2012;Yiğit and Medvedev 2012;Yuan et al 2012;Miyoshi et al 2015). The SSW impact can also extend into the summer mesosphere and mesopause region, as evidenced in observations and numerical simulations, through inter-hemispheric coupling (Becker and Fritts 2006;Karlsson et al 2007Karlsson et al , 2009aKörnich and Becker 2010;Tan et al 2012;Miyoshi et al 2015). Numerical simulations by Liu et al (2013Liu et al ( , 2014a and Miyoshi et al (2015) suggest that the SSW impact may extend into the upper thermosphere, though observations of thermospheric responses to SSW are less conclusive (Liu et al 2011;Fuller-Rowell et al 2011).…”
Section: Introductionmentioning
confidence: 99%